(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Accession of the Republic of Croatia to the EU has prompted numerous legal reforms and amendments. One of them was a major administrative court reform the main result of which was the new Administrative Disputes Act adopted in 2010 and coming into force 2012. One of the issues it regulates is the judicial control in general, and together with Foreigners Act from 2011 defines control of administrative acts and measures regarding unlawful residence of foreigners in Croatia, which is the subject of the analysis in this paper. The paper is divided in three main parts. Basic features of migrations and its consequences on European and domestic regulation are explained in the first part of the paper. Second part of the paper is focused on the procedural aspect of migrations, namely on the unlawful residence of foreigners from the perspective of the administrative courts. The final part of the paper draws certain conclusions based on the preceding analysis. The main focus of the paper is an analysis of the specificities of administrative courts’ control, such as the shortness of deadlines, oral hearings as an exception, particularities of the engagement of the parties before the court, etc. Paper elaborates in detail the normative arrangement of unlawful residence in Croatia and differences between Foreigners Act and Administrative Disputes Act through analysis of the relevant domestic and European regulative framework and case law. With this, the paper hopes to contribute in solving at least some of the numerous legal problems associated with the current migrant and refugee crisis from the perspective of the European and Croatian administrative law.